Keamanan Pesan Menggunakan Kriptografi dan Steganografi Least Significant Bit pada File Citra Digital - Dian Eka Wijayanti; Wulansari Romadlon (Universitas Negeri Gorontalo, 2022)
In the current era, data security disturbances often occur, such as data theft by unwanted people. To overcome security problems can be handled using cryptography and steganography methods. The cryptography process generates random writing that can obscure the message making it difficult for others to read. However, cryptography itself is still too weak to secure messages, so steganography is needed to disguise the existence of the message so that it is not visible to the human eye. Apart from hiding messages, another goal is to know the impact of message insertion. In this study, the encryption steps were followed by insertion and decryption followed by extraction. In the secret message encryption process using two algorithms, namely Vigenere Cipher and Playfair Cipher. In the process of inserting a secret message using Least Significant Bit (LSB) steganography. The results of the combination of cryptography and steganography are able to secure secret messages without causing significant changes even though the digital image used before and after the steganography process has increased in size, the Mean Square Error (MSE) value obtained is 0.000136 and the Peak Signal to Noise Ratio (PSNR) value is obtained. 86.8062 dB and the result of message encryption is enough to obscure the relationship pattern in the modified secret message with an avalanche effect value of 53.06%.